TINJAUAN YURIDIS TINDAK PIDANA PENGANIAYAAN TERHADAP PEJABAT NEGARA YANG SEDANG MENJALANKAN TUGAS YANG SAH DI INDONESIA - Tengku Reviandi Wahyu Samudra; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Crimes against the body and crimes against the life or commonly known as abuse and murder. The act of persecution is one of the phenomena that is difficult to disappear in social life. One of them is the mistreatment of officers who carry out their legal duties. Supposedly if you look at the legal rules contained in the Criminal Code, the perpetrator should get a heavier sentence considering this is done against an official who is carrying out duties under the order of the law or position, however the implementation of the weighting is not in accordance with the rules that have been set. The objectives of this thesis are: First, to find out the legal arrangements for the crime of mistreatment of an official when carrying out legal duties in Indonesia, Second, to find out the imposition of sanctions against perpetrators of the crime of mistreatment of an official when carrying out legal duties in Indonesia, Third, To find out the appropriate provisions for criminal sanctions against perpetrators of criminal acts of persecution against an official when carrying out legal duties in Indonesia. The author conducts research using normative juridical methods or literature studies in order to obtain secondary data through documentary studies, namely by studying and analyzing comparatively deductively on laws and regulations with theories that have a relationship with the issues studied. The results of this study, there are three main problems: First, How is the legal arrangement regarding the criminal act of mistreatment of an official when carrying out legal duties in Indonesia, Second, How is the imposition of sanctions against perpetrators of criminal acts of persecution against an official when carrying out legal duties in Indonesia, Third, what are the appropriate provisions for criminal sanctions against perpetrators of criminal acts of persecution against an official when carrying out legal duties in Indonesia. The author's suggestions in this study, Suggest that there are changes to the rules of articles that require special explanations in cases of persecution of state officials who carry out legitimate duties, Suggest that sanctions be imposed on perpetrators of persecution against state officials who carry out legitimate duties with appropriate sanctions. severe, and lastly recommends that appropriate sanctions be imposed on perpetrators of persecution against state officials who carry out legitimate duties if the impact caused by the perpetrator is not too heavy or light, it should be resolved through a restorative justice system.Keywords: Crime-Abuse-State Officials